ETNOBOTANI DAN KONSERVASI KETIMUNAN/Timonius timon (Spreng.) Merr. PADA MASYARAKAT LOKAL SUKU KANUME DI TAMAN NASIONAL WASUR PAPUA - Agung Widya; Agus Hikmat; Agus Priyono Kartono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Ethnobotany study ketimunan/Timonius Timon (Spreng.) Merr. in local communities of Kanume Tribe aims to identify the knowledge and utilization ketimunan in local communities of Kanume Tribe in Wasur National Park Papua. The research was conducted on the month in December 2014 until in February 2015 in the village of Yanggandur. Respondent conducted with quota sampling with the number of respondents 40 people. Methods of data collection is done by interviewing respondents by questionnaire. Data analysis was performed through frequency distribution. The results showed that the knowledge and utilization ketimunan in local communities of Kanume tribe rate used as medicinal plants to cure some diseases, such as abdominal pain (diarrhea), fever and stop the bleeding. The number of respondents who know ketimunan as a medicinal plant by 87.5% and not 12.5%. The number of respondents who know and can utilize ketimunan as a medicinal plant by 75% and not by 25%. In addition, the knowledge and utilization ketimunan by Kanume rate used for other purposes, namely as a substitute ingredient nut (Areca catechu L.) and a mixture of local drinks